Determinants, speed of adjustment and ownership structure of dividend policy - Shafai, Nor Anis (2019)
Dividend policy remains an unresolved puzzle in corporate finance despite the voluminous amount of past studies on the subject. Against this background, the purpose of this study is to examine the dividend behaviour by identifying the key determinants and ownership structure of dividend policy across three distinct countries with different market micro-structure; namely Singapore (developed market), Malaysia (developing market) and Saudi Arabia (emerging market) using Generalized Method of Moments. Speed of adjustment and target payout ratio are estimated by using Lintner model. The study uses data of top 100 listed firms in each country over 2007 until 2016. The results suggest that firms’ dividend policy for the three countries influenced by different determinants. For Singapore as a developed market, profitability and size are shown to significantly and positively related to dividend payout ratio, whereas leverage, business risk and growth opportunities exert significant and negative effect. Meanwhile for Malaysia (a developing market), only firm size is a significant and positive determinant. Leverage and business risk however are negatively and significantly associated to dividend payout ratio. Conversely, for Saudi Arabia as an emerging market, firm size and leverage is positively and negatively influence dividend payout ratio respectively. In term of speed of adjustment, the findings indicate that Singapore has the highest speed with low payout ratio, illustrating the constant change in the dividend payments of the listed firms in Singapore. Speed of adjustment for Malaysia is within the 50 percent range and more than 50 percent of the target payout ratio. This revealed that Malaysia firms on average pay more than 50 percent of their earnings as dividend to shareholders. In contrast, Saudi Arabia firms rapidly adjust their dividend compared to Singapore and Malaysia while the target payout ratio support the results by Lintner (1956). For ownership structure, Singaporean firms show that institutional ownership, foreign ownership and profitability have positive significant impact on dividend payout ratio. For Malaysia concentrated ownership and foreign ownership are positively related. However, the dividend payout for Saudi Arabia firms is positively affected by foreign ownership and profitability while concentrated ownership has negative impact on the dividend payout ratio. The study contribute significant inputs and effective guidelines to managers, shareholders, investors, policy makers, analysts, banks and governments in making decisions on dividend policy.